Feline umbilical cord-derived mesenchymal stem cells: isolation, identification, and antioxidative stress role through NF-κB signaling pathway - Zhai, Zhu-Hui; Li, Jun; You, Zhao; Cai, Yang; Yang, Jie; An, Jie; Zhao, Di-Peng; Wang, He-Jie; Dou, Min-Min; Du, Rong; Qin, Jian (Frontiers in Veterinary Science, 2023)
At present, the differentiation potential and antioxidant activity of feline umbilical cord-derived mesenchymal stem cells (UC-MSCs) have not been clearly studied. In this study, feline UC-MSCs were isolated by tissue adhesion method, identified by flow cytometry detection of cell surface markers (CD44, CD90, CD34, and CD45), and induced differentiation toward osteogenesis and adipogenesis in vitro. Furthermore, the oxidative stress model was established with hydrogen peroxide (H2O2) (100 μM, 300 μM, 500 μM, 700 μM, and 900 μM). The antioxidant properties of feline UC-MSCs and feline fibroblasts were compared by morphological observation, ROS detection, cell viability via CCK-8 assay, as well as oxidative and antioxidative parameters via ELISA. The mRNA expression of genes related to NF-κB pathway was detected via quantitative real-time polymerase chain reaction, while the levels of NF-κB signaling cascade-related proteins were determined via Western Blot. The results showed that feline UC-MSCs highly expressed CD44 and CD90, while negative for CD34 and CD45 expression. Feline UC-MSCs cultured under osteogenic and adipogenic conditions showed good differentiation capacity. After being exposed to different concentrations of H2O2 for eight hours, feline UC-MSCs exhibited the significantly higher survival rate than feline fibroblasts. A certain concentration of H2O2 could up-regulate the activities of SOD2 and GSH-Px in feline UC-MSCs. The expression levels of p50, MnSOD and FHC mRNA in feline UC-MSCs stimulated by 300 μM and 500 μM H2O2 significantly increased compared with the control group. Furthermore, it was observed that 500 μM H2O2 significantly enhanced the protein levels of p-IκB, IκB, p-p50, p50, MnSOD and FHC, which could be reversed by BAY 11-7082, a NF-κB signaling pathway inhibitor. In conclusion, it was confirmed that feline UC-MSCs, with good osteogenesis and adipogenesis abilities, had better antioxidant property which might be related to NF-κB signaling pathway. This study lays a foundation for the further application of feline UC-MSCs in treating the various inflammatory and oxidative injury diseases of pets.